2005
DOI: 10.1111/j.1365-2273.2005.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of recurrent acute otitis media on the quality of life of children and their caregivers

Abstract: Recurrent AOM has a considerable negative impact on the quality of life of children and causes concern to their caregivers. These effects are proportional to the severity of the condition. Professionals involved in the care of children with OM should be aware that OM not only affects physical functioning but also general well-being of the child and its family. These outcomes should therefore be included in the evaluation of the child with otitis media both in the clinical and research setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
11
40
0
2
Order By: Relevance
“…[ ( ) T D $ F I G ] Furthermore, many of the results obtained in this survey parallel those in the published scientific literature [1,9,12].…”
Section: Discussionsupporting
confidence: 78%
“…[ ( ) T D $ F I G ] Furthermore, many of the results obtained in this survey parallel those in the published scientific literature [1,9,12].…”
Section: Discussionsupporting
confidence: 78%
“…There are a multitude of surveys that assessed effect of grommets on quality of life but are difficult to compare the various quality of life instruments used by different researchers. Studies have shown there may be different findings in different populations [8,9].…”
Section: Introductionmentioning
confidence: 95%
“…There is also increasing evidence that OM has a substantial negative impact on the quality of life of patients and their families [12,23,24]. Due to the recent validation of health-related quality of life instruments for use in young children with OM [23], more data on the impact of this common infection on family life and wellbeing should become available.…”
Section: Costs and Quality Of Life Related To Ommentioning
confidence: 99%
“…Due to the recent validation of health-related quality of life instruments for use in young children with OM [23], more data on the impact of this common infection on family life and wellbeing should become available.…”
Section: Costs and Quality Of Life Related To Ommentioning
confidence: 99%